1976
DOI: 10.1038/icb.1976.28
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Microvascular Changes in Carbon Tetrachloride‐induced Cirrhotic Livers in the Rat

Abstract: Summary Liver cirrhosis was produced in the rat by combined carbon tetra‐chloride‐phenobarbitone treatment, and the microcirculation in the cirrhotic liver was observed by a quantitative in vivo transillumination technique. The total sinusoidal flow in the observed region of the cirrhotic liver did not differ significantly from that in the normal liver, despite the reduced number of sinusoids and the increased portal venous pressure. The cirrhotic liver also presented a fast‐velocity population of portal and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Hepatic microvascular changes in liver cirrhosis 3535 due to hepatitis B virus (29/39) and only few had alcoholic cirrhosis (2/39), whereas no patients with hepatitis B virus infection and nine alcoholics of 18 cirrhotic patients (women/men: 6/12) were included in a previous study [25] . Histopathological examinations have shown that in the cirrhotic liver several sinusoids become capillarized and many terminal hepatic venules are distended [32,33] : the combination of these changes may lead to low-resistivity, high-speed vascular flow, with increased inflow and outflow. In addition, intrahepatic portal veins and hepatic veins cross cirrhotic areas, leading directly or indirectly into the central venous compartment.…”
Section: Groupmentioning
confidence: 99%
“…Hepatic microvascular changes in liver cirrhosis 3535 due to hepatitis B virus (29/39) and only few had alcoholic cirrhosis (2/39), whereas no patients with hepatitis B virus infection and nine alcoholics of 18 cirrhotic patients (women/men: 6/12) were included in a previous study [25] . Histopathological examinations have shown that in the cirrhotic liver several sinusoids become capillarized and many terminal hepatic venules are distended [32,33] : the combination of these changes may lead to low-resistivity, high-speed vascular flow, with increased inflow and outflow. In addition, intrahepatic portal veins and hepatic veins cross cirrhotic areas, leading directly or indirectly into the central venous compartment.…”
Section: Groupmentioning
confidence: 99%